Analisis Peran Dimensi Kualitas Layanan Servqual Dalam Membentuk Kepuasan Konsumen - Zikri, Ahmad; Putra, Eka (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
The purpose of this study was to determine the effect of service quality on customer satisfaction at the Motor Safari Workshop in Pelalawan Regency. To achieve this goal, a research was conducted using a sample of 89 people, using a simple random sampling method (accidental random sampling). The data analysis method used simple linear regression. Based on the results of the partial t-test test, it was obtained that Service Quality had a significant effect on customer satisfaction at the Safari Motor Workshop, this was proven based on the t-test found that t-count was greater than t-table (12,423 > 1,988). The value of R. Square (R2) of 0.640 (64%) explains that the service quality variable contributes to customer satisfaction at the Safari Motor Workshop by 64%. While the remaining 36% describes other independent variables that were not observed in this study